A new species of the genus Tripylina Brzeski, 1963 (Nematoda: Enoplida: Trischistomatidae) from Zhejiang Province, eastern China - Pham, Thi Hoa; Wang, Hai Tao; Zhao, Zeng Qi; Zheng, Jing Wu (Zootaxa, 2013)
Tripylina zhejiangensis n. sp. is described and illustrated from Zhejiang province, eastern China. It has a robust body, smooth cuticle with numerous pores, two small subventral teeth in the posterior part of the large triangular dorsal tooth, one ventral-median seta in the cervical region and a pair of setae on the tail. Females are characterized by a body length of 1325–1573 µm, a = 23.3–31.2, b = 5.5–6.6, c = 13.6–19.4, c’ = 2.7–3.6 and V = 61.1–68.1%. Small subunit (SSU) and D2/D3 expansion segments of large subunit (LSU) of ribosomal DNA were used to analyze the phylogenetic relationships of sequenced species in the genus Tripylina. Tripylina zhejiangensis n. sp. varied significantly from other related nematodes both in morphological characterizations and phylogenetic analyses.